Factors for early postoperative cognitive impairment in patients after coronary bypass surgery and carotid endarterectomy - O. V. Maleva; A. S. Sosnina; E. G. Uchasova; S. V. Ivanov; O. A. Trubnikova; O. L. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. To determine the relationship between perioperative factors and cognitive function in patients after coronary bypass grafting (CABG) in combination with unilateral carotid endarterectomy (CE).Material and methods. We examined 56 men in the perioperative period with CABG combined with unilateral CE (mean age, 64,0±7,1 years). Cognitive assessment was performed before and 5-7 days after surgery with Status PF program. An advanced psychometric examination included an assessment of voluntary attention (Bourdon test), short-term memory (tests on memorizing 10 numbers, 10 words, and 10 syllables), neurodynamics (visual-motor reaction time, level of functional mobility of nervous processes, brain performance, as well as the number of errors in these tasks and missed positive signals). The concentration of neuron-specific enolase (NSE) and S100β protein in the blood serum of patients before surgery, 24 hours and 5-7 days after surgery was determined using enzyme immunoassay.Results. In the early postoperative period, an increase in reaction time (p=0,031) was accompanied by an increase in errors in this test (p=0,042) and a decrease in the number of memorized numbers (p=0,022). Twenty four hours and 5-7 days after surgery, there were no differences between the perioperative NSE level (p1-2-3>0.05). Twenty four hours after CABG surgery, the level of S100β protein increased by 9,0% (p=0,001), while regression of S100β protein to the preoperative level was observed 5-7 days after operation.Conclusion. A relationship was found between the CABG factor and the attention level (r=-0,518; p=0,031), functional mobility reaction time (r=0,476; p=0,041), and the number of errors (r=0,449; p=0,032). A correlation was found between the factor of neurochemical markers, the number of processed letters on the 1st minute of Bourdon test (r=-0,642; p=0,014), the total number of processed letters in Bourdon test (r=-0,617; p=0,017). The combined factor of perioperative period was associated with functional mobility reaction time (r=0,609; p=0,041), the number of processed letters at 4 min (r=-0,490; p=0,017), and the total number of processed letters in the Bourdon test (r=-0,334; p=0,006).